Contribution of Agama Arbitration Council as an Alternative Mode for Conflict Resolution Adopted By Shari’ah Courts in South Central Mindanao - Bagolong, Saidamin (JPAIR Multidisciplinary Research, 2023)
Issuing the Code of Muslim Personal Laws of the Philippines was a constitutional justification for the free exercise of Religion and cultural communities. This study aimed to ascertain the relationship between the contribution of the Agama Arbitration Council as an alternative mode for conflict resolution adopted by the Shari’ah Courts in South Central Mindanao. The study utilized a descriptive correlation to the 100 respondents composed of judges, clerks of courts, counselors, staff, and asatidz in the cities of Cotabato and Kidapawan, including provinces of Maguindanao, Sultan Kudarat, and North Cotabato. The researcher-made survey questionnaire was used and validated by experts, and its reliability was tested on alpha Cronbach. The Pearson r was used to analyze the data. The results found a high positive correlation between the Agama Arbitration Council as an Alternative Mode for Conflict Resolution adopted by the Shari’ah Courts in terms of divorce (talaq), subsequent marriage, and offense against customary law and its attainment of objectives on the proper conduct of arbitration procedure and the speedy disposition of cases. Hence, the Agama Arbitration Council served as a viable process instead of litigation in the regular courts. It is recommended to incorporate them as essential in the legal system of Muslims in the Philippines.